Inverse Problems and Carleman Estimates Global Uniqueness, Global Convergence and Experimental Data - Klibanov, M. V. (Michael V.) (Inverse and ill-posed problems series ;, 2021)
This book summarizes the main analytical and numerical results of Carleman estimates. In the analytical part, Carleman estimates for three main types of Partial Differential Equations (PDEs) are derived. In the numerical part, first numerical methods are proposed to solve ill-posed Cauchy problems for both linear and quasilinear PDEs. Next, various versions of the convexification method are developed for a number of Coefficient Inverse Problems.